EFFECTS OF SECTIONAL BREATHING TECHNIQUES ON OPTIMIZING PHYSIOLOGICAL PARAMETERS IN WOMEN ATHLETES - Dilli Babu, Kanchana; Murugan Senthil, Kumar; Swamynathan, Sanjaykumar (Rehabilitation and Recreation, 2025)
Background and Study Aim. Sectional breathing techniques have been associated with enhanced respiratory function and cardiovascular efficiency. This study aimed to evaluate the effectiveness of a 12-week sectional breathing intervention on improving vital capacity and reducing resting heart rate among women athletes engaged in regular sports training. Material and Methods. A simple randomized controlled trial was conducted involving 82 women players aged 18 to 23 years, randomly assigned to either the experimental group (n = 41), which practiced sectional breathing along with regular training, or the control group (n = 41), which followed regular training without additional intervention. The intervention consisted of guided sectional breathing sessions conducted twice daily (20 minutes each) for six days a week over 12 weeks. Pre– and post-intervention measurements included vital capacity (in liters) and heart rate (in beats per minute). Repeated measures ANOVA and Bonferroni pairwise comparisons were used for statistical analysis. Results. The experimental group showed a significant increase in mean vital capacity from 3.008 L (±0.287) to 3.156 L (±0.305), supported by a large effect size (F = 448.397, p = .000, η² = .847). Similarly, heart rate significantly decreased from 55.207 bpm (±6.204) to 49.951 bpm (±5.906) (F = 246.097, p = .000, η² = .752). Pairwise comparisons confirmed statistically significant differences between pre– and post-intervention measures for both outcomes. Conclusions. The findings demonstrate that sectional breathing is an effective and time-efficient strategy to enhance lung function and improve cardiovascular efficiency in women athletes. Incorporating such respiratory training into regular sports routines may offer measurable health and performance benefits.